Usefulness of Plasma Galectin-3 Levels in Systolic Heart Failure to Predict Renal Insufficiency and Survival - Tang, W.H. Wilson; Shrestha, Kevin; Shao, Zhili; Borowski, Allen G.; Troughton, Richard W.; Thomas, James D.; Klein, Allan L. (The American journal of cardiology, 2011)
Galectin-3 plays an important role in fibroblast activation and fibrosis in animal models. Increased galectin-3 levels are associated with poor long-term survival in heart failure (HF). We examined the relation between plasma galectin-3 levels and myocardial indexes of systolic HF. We measured plasma galectin-3 in 133 subjects with chronic HF and 45 with advanced decompensated HF using echocardiographic and hemodynamic evaluations. In the chronic HF cohort, median plasma galectin-3 level was 13.9 ng/ml (interquartile range 12.1 to 16.9). Higher galectin-3 was associated with more advanced age (r = 0.22, p = 0.010), poor renal function (estimated glomerular filtration rate, r = −0.24, p = 0.007; cystatin C, r = 0.38, p <0.0001) and predicted all-cause mortality (hazard ratio 1.86, 95% confidence interval 1.36 to 2.54, p <0.001). In multivariate analysis, galectin-3 remained an independent predictor of all-cause mortality after adjusting for age, estimated glomerular filtration rate, left ventricular (LV) ejection fraction, and mitral early diastolic myocardial relaxation velocity at septal mitral annulus (hazard ratio 1.94, 95% confidence interval 1.30 to 2.91, p = 0.001). However, galectin-3 did not predict the combined end point of all-cause mortality, cardiac transplantation, or HF hospitalization (p >0.05). Furthermore, there were no relations between galectin-3 and LV end-diastolic volume index (r = −0.05, p = 0.61), LV ejection fraction (r = 0.10, p = 0.25), or LV diastolic function (mitral early diastolic myocardial relaxation velocity at septal mitral annulus, r = 0.06, p = 0.52; left atrial volume index, r = 0.08, p = 0.41). In the advanced decompensated HF cohort, we did not observe any relation between galectin-3 and echocardiographic or hemodynamic indexes. In conclusion, high plasma galectin-3 levels were associated with renal insufficiency and poorer survival in patients with chronic systolic HF. However, we did not observe a relation between galectin-3 and echocardiographic or hemodynamic indexes.